2022
DOI: 10.1001/jamanetworkopen.2022.9401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Estimated Incentives for Preventing Postpartum Depression in Value-Based Payment Models Using the Net Present Value of Care vs Total Cost of Care

Abstract: Key Points Question Do value-based payment (VBP) models that share 50% of the 5-year expected health care savings estimated by reduced postpartum depression incidence offer larger incentives for clinicians to prevent postpartum depression than traditional VBP models that share 100% of 1-year actual savings? Findings In this decision analytical model with a simulated cohort of 1000 pregnant individuals enrolled in Medicaid, sharing estimated savings offered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“… 37 Another study estimated that group counselling (costing £114 per mother) cost around £73 □ less than individual counselling (£187 per mother) for mothers with PND. 36 This study found that screening for PND costs less than £2 per mother. 36 Studies that combined screening for PND with an intervention were also found to be cost-effective, resulting in 29 more healthy women at a cost of £938 □□ per woman.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“… 37 Another study estimated that group counselling (costing £114 per mother) cost around £73 □ less than individual counselling (£187 per mother) for mothers with PND. 36 This study found that screening for PND costs less than £2 per mother. 36 Studies that combined screening for PND with an intervention were also found to be cost-effective, resulting in 29 more healthy women at a cost of £938 □□ per woman.…”
Section: Discussionmentioning
confidence: 73%
“… 36 This study found that screening for PND costs less than £2 per mother. 36 Studies that combined screening for PND with an intervention were also found to be cost-effective, resulting in 29 more healthy women at a cost of £938 □□ per woman. 38 The ICERs of the intervention branch compared with usual care were $13 857 per QALY gained (below the commonly accepted willingness-to-pay threshold of $50 000 per QALY gained) and $10 182 per remission achieved.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Longitudinal studies also show an increased risk of depression and anxiety in teenage years [25]. The financial cost of untreated perinatal depression is over 14 billion USD yearly [26] due to associated missed work/lack of productivity and treatment for perinatal depression itself [27] as well as the resulting comorbidities such as cardiovascular disease and hypertension [28] [29].…”
Section: Introductionmentioning
confidence: 99%